The value of \[\mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}}\] is
(a)1
(b)\[\dfrac{3}{2}\]
(c)\[\dfrac{5}{6}\]
(d)\[\dfrac{7}{{12}}\]
Answer
Verified
480.3k+ views
Hint: Here, we will first use the formulae of sums, \[\sum {{n^2}} = \dfrac{{n\left( {n + 1} \right)\left( {n + 2} \right)}}{6}\], \[\sum {{n^3}} = {\left[ {\dfrac{{n\left( {n + 1} \right)}}{2}} \right]^2}\] and \[\sum {{n^6}} = \dfrac{1}{{42}}\left( {6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n} \right)\] in the given expression and then taking \[n \to \infty \] on right hand side of the above equation, \[\dfrac{1}{n} \to 0\] to find the required value.
Complete step-by-step answer:
We are given \[\mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}}\].
Using the formulae of sums, \[\sum {{n^2}} = \dfrac{{n\left( {n + 1} \right)\left( {n + 2} \right)}}{6}\], \[\sum {{n^3}} = {\left[ {\dfrac{{n\left( {n + 1} \right)}}{2}} \right]^2}\] and \[\sum {{n^6}} = \dfrac{1}{{42}}\left( {6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n} \right)\] in the above expression, we get
\[
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left[ {\dfrac{{n\left( {n + 1} \right)\left( {n + 2} \right)}}{6}} \right]{{\left[ {\dfrac{{n\left( {n + 1} \right)}}{2}} \right]}^2}}}{{\left[ {\dfrac{{6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n}}{{42}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left[ {\dfrac{{2{n^3} + 3{n^2} + n}}{6}} \right]\left[ {\dfrac{{{n^4} + 2{n^3} + {n^2}}}{4}} \right]}}{{\left[ {\dfrac{{6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n}}{{42}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \dfrac{{\left[ {\dfrac{{\left( {2{n^3} + 3{n^2} + n} \right)\left( {{n^4} + 2{n^3} + {n^2}} \right)}}{{24}}} \right]}}{{\left[ {\dfrac{{6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n}}{{42}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{42\left[ {2{n^7} + 4{n^6} + 3{n^6} + 6{n^5} + 3{n^4} + {n^5} + 2{n^4} + {n^3}} \right]}}{{24\left[ {6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{7\left[ {2{n^7} + 4{n^6} + 3{n^6} + 6{n^5} + 3{n^4} + {n^5} + 2{n^4} + {n^3}} \right]}}{{4\left[ {6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n} \right]}} \\
\]
Dividing the numerator and denominator by \[{n^7}\] in right side of the above equation, we get
\[
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{7\left[ {\dfrac{{2{n^7} + 4{n^6} + 3{n^6} + 6{n^5} + 3{n^4} + {n^5} + 2{n^4} + {n^3}}}{{{n^7}}}} \right]}}{{4\left[ {\dfrac{{6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n}}{{{n^7}}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{7\left[ {\dfrac{{2{n^7}}}{{{n^7}}} + \dfrac{{4{n^6}}}{{{n^7}}} + \dfrac{{2{n^5}}}{{{n^7}}} + \dfrac{{3{n^6}}}{{{n^7}}} + \dfrac{{6{n^5}}}{{{n^7}}} + \dfrac{{3{n^4}}}{{{n^7}}} + \dfrac{{{n^5}}}{{{n^7}}} + \dfrac{{2{n^4}}}{{{n^7}}} + \dfrac{{{n^3}}}{{{n^7}}}} \right]}}{{4\left[ {\dfrac{{6{n^7}}}{{{n^7}}} + \dfrac{{21{n^6}}}{{{n^7}}} + \dfrac{{21{n^5}}}{{{n^7}}} - \dfrac{{7{n^3}}}{{{n^7}}} + \dfrac{n}{{{n^7}}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{7\left[ {2 + \dfrac{4}{n} + \dfrac{2}{{{n^2}}} + \dfrac{3}{n} + \dfrac{6}{{{n^2}}} + \dfrac{3}{{{n^3}}} + \dfrac{1}{{{n^2}}} + \dfrac{2}{{{n^3}}} + \dfrac{1}{{{n^4}}}} \right]}}{{4\left[ {6 + \dfrac{{21}}{n} + \dfrac{{21}}{{{n^2}}} - \dfrac{7}{{{n^4}}} + \dfrac{1}{{{n^6}}}} \right]}} \\
\]
When taking \[n \to \infty \] on right hand side of the above equation, \[\dfrac{1}{n} \to 0\], we get
\[
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \dfrac{{7\left[ {2 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0} \right]}}{{4\left[ {6 + 0 + 0 - 0 + 0} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \dfrac{{7 \cdot 2}}{{4 \cdot 6}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \dfrac{7}{{12}} \\
\]
Note: Whenever we face such types of questions on summation problems, students must remember the basic summation formulae of the series. Students must not get confused with the values of sums, as the main part of the question will be over then.
Complete step-by-step answer:
We are given \[\mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}}\].
Using the formulae of sums, \[\sum {{n^2}} = \dfrac{{n\left( {n + 1} \right)\left( {n + 2} \right)}}{6}\], \[\sum {{n^3}} = {\left[ {\dfrac{{n\left( {n + 1} \right)}}{2}} \right]^2}\] and \[\sum {{n^6}} = \dfrac{1}{{42}}\left( {6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n} \right)\] in the above expression, we get
\[
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left[ {\dfrac{{n\left( {n + 1} \right)\left( {n + 2} \right)}}{6}} \right]{{\left[ {\dfrac{{n\left( {n + 1} \right)}}{2}} \right]}^2}}}{{\left[ {\dfrac{{6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n}}{{42}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left[ {\dfrac{{2{n^3} + 3{n^2} + n}}{6}} \right]\left[ {\dfrac{{{n^4} + 2{n^3} + {n^2}}}{4}} \right]}}{{\left[ {\dfrac{{6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n}}{{42}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \dfrac{{\left[ {\dfrac{{\left( {2{n^3} + 3{n^2} + n} \right)\left( {{n^4} + 2{n^3} + {n^2}} \right)}}{{24}}} \right]}}{{\left[ {\dfrac{{6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n}}{{42}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{42\left[ {2{n^7} + 4{n^6} + 3{n^6} + 6{n^5} + 3{n^4} + {n^5} + 2{n^4} + {n^3}} \right]}}{{24\left[ {6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{7\left[ {2{n^7} + 4{n^6} + 3{n^6} + 6{n^5} + 3{n^4} + {n^5} + 2{n^4} + {n^3}} \right]}}{{4\left[ {6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n} \right]}} \\
\]
Dividing the numerator and denominator by \[{n^7}\] in right side of the above equation, we get
\[
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{7\left[ {\dfrac{{2{n^7} + 4{n^6} + 3{n^6} + 6{n^5} + 3{n^4} + {n^5} + 2{n^4} + {n^3}}}{{{n^7}}}} \right]}}{{4\left[ {\dfrac{{6{n^7} + 21{n^6} + 21{n^5} - 7{n^3} + n}}{{{n^7}}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{7\left[ {\dfrac{{2{n^7}}}{{{n^7}}} + \dfrac{{4{n^6}}}{{{n^7}}} + \dfrac{{2{n^5}}}{{{n^7}}} + \dfrac{{3{n^6}}}{{{n^7}}} + \dfrac{{6{n^5}}}{{{n^7}}} + \dfrac{{3{n^4}}}{{{n^7}}} + \dfrac{{{n^5}}}{{{n^7}}} + \dfrac{{2{n^4}}}{{{n^7}}} + \dfrac{{{n^3}}}{{{n^7}}}} \right]}}{{4\left[ {\dfrac{{6{n^7}}}{{{n^7}}} + \dfrac{{21{n^6}}}{{{n^7}}} + \dfrac{{21{n^5}}}{{{n^7}}} - \dfrac{{7{n^3}}}{{{n^7}}} + \dfrac{n}{{{n^7}}}} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \mathop {\lim }\limits_{n \to \infty } \dfrac{{7\left[ {2 + \dfrac{4}{n} + \dfrac{2}{{{n^2}}} + \dfrac{3}{n} + \dfrac{6}{{{n^2}}} + \dfrac{3}{{{n^3}}} + \dfrac{1}{{{n^2}}} + \dfrac{2}{{{n^3}}} + \dfrac{1}{{{n^4}}}} \right]}}{{4\left[ {6 + \dfrac{{21}}{n} + \dfrac{{21}}{{{n^2}}} - \dfrac{7}{{{n^4}}} + \dfrac{1}{{{n^6}}}} \right]}} \\
\]
When taking \[n \to \infty \] on right hand side of the above equation, \[\dfrac{1}{n} \to 0\], we get
\[
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \dfrac{{7\left[ {2 + 0 + 0 + 0 + 0 + 0 + 0 + 0 + 0} \right]}}{{4\left[ {6 + 0 + 0 - 0 + 0} \right]}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \dfrac{{7 \cdot 2}}{{4 \cdot 6}} \\
\Rightarrow \mathop {\lim }\limits_{n \to \infty } \dfrac{{\left( {\sum {{n^2}} } \right)\left( {\sum {{n^3}} } \right)}}{{\left( {\sum {{n^6}} } \right)}} = \dfrac{7}{{12}} \\
\]
Note: Whenever we face such types of questions on summation problems, students must remember the basic summation formulae of the series. Students must not get confused with the values of sums, as the main part of the question will be over then.
Recently Updated Pages
How to find how many moles are in an ion I am given class 11 chemistry CBSE
Class 11 Question and Answer - Your Ultimate Solutions Guide
Identify how many lines of symmetry drawn are there class 8 maths CBSE
State true or false If two lines intersect and if one class 8 maths CBSE
Tina had 20m 5cm long cloth She cuts 4m 50cm lengt-class-8-maths-CBSE
Which sentence is punctuated correctly A Always ask class 8 english CBSE
Trending doubts
The reservoir of dam is called Govind Sagar A Jayakwadi class 11 social science CBSE
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE